Organizational Structure of Private Higher Education Institutions and Their Development Patterns - Sa’diyah, Rifka Rofidah; Aprilya, Eka; Wahjono, Sentot Imam (Golden Ratio of Data in Summary, 2025)
Organizational structure is a framework that regulates the relationship between parts in an organization to achieve common goals. In higher education, organizational structure is important in determining operational effectiveness and achieving the institution's vision. This study discusses the patterns or methods used in developing organizational structures at the University of Indonesia Maju (UIMA) in response to the change from the Indonesian Health Sciences College (STIKIM) to a university. The study aimed to understand the basics of compiling organizational structures at UIMA. The method used was a qualitative approach. The study results showed that the development of organizational structures at UIMA followed Mintzberg's theoretical guidelines, which consisted of five elements: The Strategic Apex, The Middle Line, The Technostructure, The Support Staff, and The Operating Core. Therefore, it can be concluded that this study confirms that UIMA's organizational structure is based on Mintzberg's theory, and further evaluations regarding the effectiveness of organizational structures in achieving UIMA's vision are recommended.